MCU NODE BASED BLOOD GROUP DETECTION EQUIPPED WITH AN AUTOMATIC SAMPLE STIRER - Fatimang, St.; Rusmin, Nur Fadil (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
Blood type detection tool is a tool that can help In reading blood groups, you can find out the type of group blood with use sensors Light And LED, so in use tool This be equipped Gearboxes as stirrer sample automatic Which Where fluid reagent antisera will stirred with sample blood using the ABO method, results in sensor readings will be displayed on the LCD and also on the application when using Nodes MCU as the microcontroller, based on results testing tool This use 3 person with group blood Which The same on each Blood group samples are A, B, AB, O by comparing groups blood on card identity And results testing Which Where the result can obtained results Which The same. With mark flat flat group blood A is 0.6 and 2.1. As for blood type B, it is 1.7 and 1.1. As for AB blood type is 0.9 and 1.1. And blood type O is 2,3 And 2,3. whereas For mark error Which obtained group blood A that is 0.5 error value for blood group B i.e. 0.5 error value for blood group AB i.e 0.6, And error value for blood type O namely 0.2.